Abstract 190: Patient Selection for Intracranial Stenting: Impact on Clinical Outcomes and Procedural Success Rates - Michael John McAree (Stroke: Vascular and Interventional Neurology)
Introduction Intracranial atherosclerosis (ICAS) is a leading global cause of stroke. The role of intracranial stenting in ICAS remains uncertain. In the SAMMPRIS trial, patients who had experienced recent TIA/CVA secondary to 70‐99% ICAS demonstrated an increased risk of recurrent stroke when treated with angioplasty and stenting compared to medical therapy alone [1]. The VISSIT trial found an increased 12‐month risk of TIA/CVA in the same territory, as well as an increased 30‐day risk of any TIA/CVA, when a stenting was used in patients with ICAS [2]. Additionally, the recent CASSISS trial demonstrated that adding percutaneous transluminal angioplasty and stenting (PTAS) to medical therapy did not significantly affect the risk of stroke or death within 30 days or stroke beyond 30 days through 1 year in patients TIA/CVA secondary to symptomatic ICAS [3]. However, the WEAVE trial demonstrated that using the Wingspan stent for ICAS resulted in a low periprocedural complication rate and excellent safety profile [4]. Subsequently, the WOVEN study provided a 1‐year follow‐up to WEAVE. It presented a more homogeneous patient group than in prior studies, and demonstrated a relatively low 8.5% 1‐year rate of stroke and death in stented patients [5]. Currently underway, the Angioplasty and Stenting for Patients With Symptomatic Intracranial Atherosclerosis Clinical trial (NCT02689037) aims to determine whether PTAS combined with medical treatment is superior to medical treatment alone in preventing stroke and death events in patients with symptomatic ICAS [6]. The purpose of this case series is to provide an overview of the procedural and clinical outcomes of patients who underwent stenting for symptomatic ICAS. Methods We reviewed a database of all interventional procedures conducted at our institution to identify patients who underwent intracranial stenting from 2013 and 2022 for symptomatic ICAS. Electronic medical records were assessed, and data on patient demographics, comorbidities, lesion characteristics, and clinical outcomes were extracted. The outcomes of interest included successful stent placement, restoration of blood flow, procedural complications, symptomatic improvement, change in NIHSS, and mortality and stroke within one year. Descriptive statistics were used, summarizing continuous variables as means and standard deviations, and categorical variables as frequencies and ranges. Results Between 2013 and 2022, 35 patients underwent intracranial stenting for symptomatic ICAS. Procedurally, all patients had successful stent placement and restoration of blood flow. Six patients (17.1%) experienced perioperative complications including stent occlusion, bradycardia, and hematoma. Regarding clinical outcomes, 25 patients (71.4%) showed improvement in their TIA/CVA symptoms, including dizziness, weakness, and speech difficulties. Furthermore, 21 patients (60%) had improved NIHSS scores by discharge, 9 patients (25.7%) remained stable, and 4 patients (11.4%) deteriorated. One unrelated mortality was recorded at 1‐year post‐procedure. Conclusion This case series demonstrates the successful and effective restoration of distal blood flow through intracranial stenting for symptomatic ICAS. The low rates of perioperative complications and potential improvements in patients' clinical outcomes suggest the need for further investigation into the patient selection, safety, and effectiveness of intracranial stenting for managing symptomatic ICAS.